2009
DOI: 10.1021/ie900176y
|View full text |Cite
|
Sign up to set email alerts
|

Wall Effects on a Sphere Falling in Quiescent Power Law Fluids in Cylindrical Tubes

Abstract: The effect of finite boundaries on the drag experienced by a sphere settling in quiescent power law fluids in cylindrical vessels has been investigated numerically. In particular, the momentum equations have been solved numerically over the following ranges of conditions: sphere Reynolds number, 1-100; power law index, 0.2-1; and sphere-to-tube diameter ratio, 0-0.5. Due to the backflow of the fluid caused by a falling sphere and the corresponding changes in the velocity field close to the sphere, the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 41 publications
8
56
1
Order By: Relevance
“…Therefore, the expression of the viscous resistance should be revised. It should be indicated that the most widely used expression is the Faxon correction formula as the following [16]: truefw=1-2.104d/D+2.09(d/D)3-0.95(d/D)5 trueηs=fwη …”
Section: Experimental Designmentioning
confidence: 99%
“…Therefore, the expression of the viscous resistance should be revised. It should be indicated that the most widely used expression is the Faxon correction formula as the following [16]: truefw=1-2.104d/D+2.09(d/D)3-0.95(d/D)5 trueηs=fwη …”
Section: Experimental Designmentioning
confidence: 99%
“…Results presented in the work of Rajasekhar and Kishore [33] with  = 5 are also cited in Table 3, showing differences of ~ 96% at Re = 1 and up to ~ 124% at Re = 100 from present work. For a power law fluid of n = 0.4, predicted results were compared with literature [32] in term of normalised drag coefficient, which was normalised by the corresponding values in Newtonian fluids at same  and Re. Good consistency is shown at Re = 1, 10 and 100, respectively, as indicated in Table 4.…”
Section: Validations In Bounded Newtonian and Shear-thinning Fluidsmentioning
confidence: 99%
“…Machač and Lecjaks [ 11 ] and Malhotra and Sharma [ 12 ] established wall factor correlations for spheres settling through power law fluids and surfactant-based shear thinning viscoelastic fluids in rectangular ducts and parallel plates. Kawase and Ulbrecht [ 13 ], Missirlis et al [ 14 ], and Song et al [ 15 ] theoretically studied and numerically simulated the settling velocity of a sphere in bound non-Newtonian fluid. It is now widely accepted that the elasticity and shear thinning behavior of non-Newtonian fluids reduce the retardation effect of the confining walls.…”
Section: Introductionmentioning
confidence: 99%